The Effect of Rock Phosphate Fertilizer application Urea, MOP, and Dolomite on leaf Phosphorus Content of Produce Palm Oil in Ultisol - Tomy Fadillah; Hamidah Hanum; Madjid Damanik (Jurnal Agroekoteknologi, 2018)
The aim of the research wasto examine the effect of application rock phosphate, urea, MOP, and dolomite on leaf P content of produce palm oil and see the dynamics of leaf P content of produce palm oil after 6 months of fertilizer application in Ultisol. The research was implemented inPPKS Kebun Aek Pancur Tanjung Morawa using non factorial randomized block design with treatment T0 (without fertilizer), T1 (rock phosphate), T2 (rock phosphate and urea), T3 (rock phosphate and MOP), T4 (rock phosphate and Dolphite), T5 (rock phosphate, urea, and MOP), T6 (rock phosphate, urea, and dolomite), T7 (rock phosphate, MOP, and dolomite), T8 (rock phosphate, urea, MOP, and dolomite), with 3 replications. Parameters measured are P leaf. Result of this research showed that application of rock phosphate, urea, MOP, and dolomite did not affect leaf P content for 6 months after application.   Keywords :palm oil,P leaf,rock phosphate, Ultisol